Jet mass and substructure of inclusive jets in root s=7 TeV pp collisions with the ATLAS experiment - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2012)
Recent studies have highlighted the potential of jet substructure techniques to identify the hadronic decays of boosted heavy particles. These studies all rely upon the assumption that the internal substructure of jets generated by QCD radiation is well understood. In this article, this assumption is tested on an inclusive sample of jets recorded with the ATLAS detector in 2010, which corresponds to 35 pb -1 of pp collisions delivered by the LHC at Rs = 7TeV.